Functional role of respiratory supercomplexes in mice: SCAF1 relevance and segmentation of the Q(pool) - Calvo, Enrique (Sci Adv, 2020)
Mitochondrial respiratory complexes assemble into supercomplexes (SC). Q-respirasome (III(2) + IV) requires the supercomplex assembly factor (SCAF1) protein. The role of this factor in the N-respirasome (I + III(2) + IV) and the physiological role of SCs are controversial. Here, we study C57BL/6J mice harboring nonfunctional SCAF1, the full knockout for SCAF1, or the wild-type version of the protein and found that exercise performance is SCAF1 dependent. By combining quantitative data–independent proteomics, 2D Blue native gel electrophoresis, and functional analysis of enriched respirasome fractions, we show that SCAF1 confers structural attachment between III(2) and IV within the N-respirasome, increases NADH-dependent respiration, and reduces reactive oxygen species (ROS). Furthermore, the expression of AOX in cells and mice confirms that CI-CIII superassembly segments the CoQ in two pools and modulates CI-NADH oxidative capacity.